Decursinol angelate relieves inflammatory bowel disease by inhibiting the ROS/TXNIP/NLRP3 pathway and pyroptosis - Wang, Yudi; Wang, Jiamin; Chen, Yonghu; Li, Xuezheng; Jiang, Zhe (Frontiers in Pharmacology, 2025)
IntroductionDespite evidence of the efficacy of decursinol angelate (DA), a prescription medication derived farom traditional Chinese medicine, in alleviating inflammatory bowel disease (IBD), the precise mechanisms behind its action remain unclear.MethodsLipopolysaccharides (LPS) and dextran sodium sulfate (DSS) induction were used as in vitro and in vivo models of IBD, respectively, to assess the role of DA in alleviating IBD. Enzyme-linked immunosorbent assay (ELISA) was performed to detect the expression levels of pro-inflammatory cytokines in mouse serum, Western blot was performed to detect the expression of TXNIP/NLRP3 pathway tight junction (TJ) proteins in colon tissues and cells, and immunohistochemistry, immunofluorescence and immunohistochemistry, immunofluorescence and qRT-PCR were used to validate the proteins related to this signaling pathway. Molecular docking technique and co-immunoprecipitation (Co-IP) method assay were applied to evaluate the targeting effect of DA on NLRP3 proteins, and MCC950, a specific inhibitor of NLRP3, was used as a positive control for validation.ResultsOur research indicates that DA’s distinctive molecular mechanism could entail binding to the NLRP3 protein, thereby suppressing the activation of the NLRP3 pathway and diminishing the assembly and activation of the NLRP3 inflammasome, thus functioning as an anti-inflammatory agent.ConclusionDA may play a role in improving BD by inhibiting the activation of the ROS/TXNIP/NLRP3 signaling pathway and the release of inflammatory mediators, and by repairing the intestinal barrier function.